Speech Act Strategies of Commands and Prohibitions in Hadiths - Ahmad Jazuli (Arabic Literature Department, 2020)
The aim of this article is to explain the strategy of speech acts of the commands and prohibitions of the prophet Muhammad in the hadith using Searle's speech acts theory. The purpose of this paper is focused on describing the strategies used by the prophet Muhammad in conveying commands and prohibitions. The results of this paper indicate that there are many speech act strategies used by the Prophet Muhammad in delivering commands and prohibitions, such as direct literal speech acts, indirect literal speech acts, and indirect literal speech acts.